Digital inclusion for a sustainable future: Catalysing green economic growth - Oleksii Lyulyov; Tetyana Pimonenko; Aleksy Kwilinski (Sustainable Futures)
Digital inclusion and green economic development are increasingly intertwined, as societies face the dual challenges of advancing technological innovation and addressing environmental sustainability. This study investigates the nonlinear dynamics between digital inclusion and green economic development via a panel dataset of 27 European Union (EU) member states from 2013–2022. The analysis employs the global Malmquist–Luenberger (GML) productivity index to measure green economic development, integrating desirable outputs such as GDP with undesirable outputs. A baseline regression model is used to explore the relationship between digital inclusion and green economic development, which is further validated through robustness checks via Panel-Corrected Standard Errors (PCSE) and Feasible Generalized Least Squares (FGLS). The results reveal a U-shaped nonlinear relationship between digital inclusion and green economic productivity. Initial investments in digital inclusion have limited or even adverse effects due to infrastructure development costs and increased energy consumption. However, as digital inclusion intensifies, the benefits become significant, enhancing eco-friendly practices, resource efficiency, and public engagement in sustainability initiatives. The baseline regression coefficients indicate that for every 1 % increase in digital inclusion, green economic productivity initially decreases by 1.72 % but subsequently improves by 0.22 % when the index surpasses a critical threshold. The robustness models confirm these findings, with the results of the FGLS showing an even stronger positive impact of digital inclusion on green productivity at higher levels. EU policymakers should prioritize targeted investments in digital infrastructure in regions lagging in digital inclusion, ensuring equitable access to technologies that foster green practices. The policies should incentivize digital innovations such as smart grids, waste reduction platforms, and sustainable transportation systems to amplify the positive impacts of digitalization. For example, expanding broadband access in underperforming regions could lead to a 5–7 % improvement in green productivity on the basis of the observed data. Cross-border collaboration within the EU is essential for sharing best practices and fostering synergies between digital and green transitions.